Health screening to identify opportunities to improve preventive medicine in cats and dogs. (11th May 2015) - Diez, M.; Picavet, P.; Ricci, R.; Dequenne, M.; Renard, M.; Bongartz, A.; Farnir, F.
<x xml:space="preserve">Abstract</x> OBJECTIVES To describe the results of a prevention campaign in terms of participation and pet health status and to identify opportunities to improve preventive medicine in cats and dogs. METHODS An awareness campaign was designed to highlight the role of veterinarians and emphasise the benefits of a veterinary visit. Owners were invited to make an appointment for a free pet health check in a voluntarily participating veterinary clinic. Observations recorded by the veterinarians were entered in a database and subsequently analysed using simple descriptive statistics. RESULTS A total of 5305 completed health check forms were analysed. The percentages of overweight and obese dogs and cats were 34 and 36%, respectively; this was the most common finding, followed by dental calculus (31% in dogs, 21% in cats). In total 67% of cats did not undergo flea control and 59% were not vaccinated. CLINICAL SIGNIFICANCE Opportunities for increased quality of care are numerous given the high percentage of intact, unvaccinated or non‐permanently identified pets and the low level of worm and flea control. Animal health should benefit from preventive measures, and improved management can be undertaken after early detection of diseases.